درجة استخدام أساتذة التعليم المتوسط لأدوات التقويم المستمر من وجهة نظرهم دراسة ميدانية ببعض متوسطات ولاية المسيلة (مجلة الواحات للبحوث والدراسات, 2022)
ملخصهدفت هذه الدراسة إلى التعرف على درجة استخدام أساتذة التعليم المتوسط لأدوات التقويم المستمر من وجهة نظرهم، حيث تم استخدام المنهج الوصفي، كما تم استخدام استبيان مكون من تسع فقرات تمثل أدوات التقويم المستمر، وقد تكونت عينة الدراسة من (446) أستاذا وأستاذة اختيرت بطريقة عشوائية عنقودية، وتم استخدام مجموعة من الأساليب الإحصائية تمثلت في المتوسطات الحسابية والانحرافات المعيارية، واختبار (t). وتوصلت الدراسة إلى أن درجة استخدام أساتذة التعليم المتوسط لأدوات التقويم المستمر من وجهة نظرهم كانت متوسطة، وأنه لا توجد فروق ذات دلالة إحصائية في درجة استخدام أساتذة التعليم المتوسط لأدوات التقويم المستمر من وجهة نظرهم تعزى لمتغير الجنس. كلمات دالة: التقويم المستمر , أدوات التقويم المستمر , أساتذة التعليم المتوسط.               Abstract This study aimed to identify the degree to which middle school teachers use continuous evaluation tools from their point of view, as the descriptive approach was used, and a questionnaire consisting of nine items representing continuous evaluation tools was used, and the study sample consisted of (446) teachers chosen in a random cluster method. , And a set of statistical methods were used, represented by the arithmetic means, standard deviations, and t-test. The study found that the degree of middle school teachers 'use of continuous evaluation tools from their point of view was intermediate, and that there were no statistically significant differences in the degree of middle school teachers use of continuous evaluation tools from their point of view due to the gender variable. Key words: continuous evaluation, continuous evaluation tools, middle school teachers.